METAZOANS PARASITES OF “CHUB MACKEREL” SCOMBER JAPONICUS HOUTTUYN, 1782 (PERCIFORMES: SCOMBRIDAE) AT THE PORT OF CHICAMA, LA LIBERTAD, PERU - Cruces, Celso (2014)
This study quantifies the metazoan parasites of 31 "chub mackerel" Scomber japonicus from the Puerto Chicama, La Libertad, Peru during 2014. 12 parasite species were recorded. Ectoparasites were: Clavellisa scombri and Ceratothoa gaudichaudii. Endoparasites were Prodistomum orientalis, Koellikeria sp., Maccallumtrema sp., Didimozoidea gen sp., Ovarionematobothrium saba, Nematobothrium scombri, Scolex pleuronectis, Anisakis simplex, Contracaecum sp. and Rhadinorhynchus pristis. The three most prevalent parasites and mean abundance were S. pleuronectis, O. saba and N. scombri. The parasites showed an aggregated distribution. The total length of S. japonicus showed no association with the prevalence and abundance of parasitic fauna. Only the prevalence and abundance of O. saba was relatedto host sex. The values of condition factor (k ) and gonadosomatic index (GSI) between parasitized and non-parasitized of n S. japonicus showed differences for O. saba and for S. pleuronectis, respectively. Diversity indices of richness and evenness of the community component and parasitic infracommunity of S japonicus showed high values, being higher in the infracommunity. Differences between the sexes of fish for parasitic infracommunity were observed only to indices of species richness. The richness estimator indicated an expected value of 25% more parasitic species. Comparing the prevalence of parasites of S. japonicus between Port of Callao (2002-2003, Central Coast of Peru) and the Port of Chicama, La Libertad (2014, North Coast of Peru) show significant differences of 61% of the parasites evaluated. Similarity indices of the parasitic fauna between 2002-2003 and 2014 indicated very low values.